Assessment of The Utilization of Electronic Resouces Among Pre-Service Teachers in College of Education in Kwara State - Olafare Oladimeji Festus; Oyeronke Olufunmilola Ogunlande (IJER (Indonesian Journal of Educational Research), 2018)
Electronic resources are those data resources that can only be accessed through the internet with the use of computers and other ICT devices. The study was embarked upon to assess the level of utilization of e-resources by pre-service teachers in Colleges of Education in Kwara State. It employed descriptive survey research design. Using purposive sampling method, a total of 150 pre-service teachers from two colleges of education in Kwara state were selected. A researcher designed questionnaire, “e-resources utilization by pre-service teachers” (ERUPT) validated by educational technology experts was used to obtain relevant data. Analysis of data was done using descriptive statistics inform of mean and percentages. The study found that majority of the pre-service teachers were aware of the availability of electronic resources in the library. More than half of them did not make regular use of the resources. The major challenges include: poor network/internet connectivity, limited access to computer terminals, poor familiarity with the tools, too much information, lack of IT knowledge, inadequate power supply, among others. The study made some recommendations based on the findings of the study.